P 30. Evoking language errors using online paired-pulse TMS – A proof-of-principle study. Issue 8 (August 2021) - Nettekoven, C.; Pieczewski, J.; Neuschmelting, V.; Jonas, K.; Goldbrunner, R.; Grefkes, C.; Weiß Lucas, C.
Abstract : Objective. The individual cortical representation of language areas can be assessed non-invasively using repetitive transcranial magnetic stimulation (rTMS). We recently showed that rTMS with a frequency of 30 Hz is superior to the most commonly used protocol of (5-)10 Hz. However, rTMS protocols still suffer from a relatively low number of evoked language errors and the sensory discomfort evoked by the stimulation, highlighting the need for improved stimulation protocols. We, therefore, tested whether paired pulse (pp-)TMS is also suitable for inducing language errors. Methods. 13 healthy, right-handed subjects ( f  = 6, 25–41 years) were investigated using two different rTMS protocols: (i) the 30 Hz rTMS as control and (ii) the novel pp-TMS (interstimulus-interval: 7 ms). TMS protocols were applied in a pseudo-randomized order during a picture naming task (picture-to-trigger interval: 0 ms) over cortical language areas. Language errors were post-hoc analysed by two independent raters and were assigned to eight different error categories. The level of pain was assessed on a subjective 0–10 numeric rating scale (NRS). Results. 30 Hz rTMS evoked a significantly higher number of errors than the pp-protocol, i.e., 18 ± 12 % vs 10 ± 7 % ( p  < 0.05). However, pp-TMS was significantly better tolerated with a mean NRS of 2.3 ± 1.6 vs 3.4 ± 1.5 ( p  < 0.05, FDR-corrected). Of note, pp-TMS could induce a higher number of anomias (15 ± 15 %) than 30 Hz rTMS (4 ± 7 %; p  < 0.1, FDR-corrected). Conclusion. We could show that single pp-TMS is capable of inducing language errors whilst being well-tolerated by the subjects. Therefore, pp-TMS might be an alternative protocol for language mapping, especially when considering safety aspects. Nevertheless, the pp-TMS protocol needs to be further evaluated to optimize its potential use also in preoperative language mapping.